The National Hospital Discharge Survey and Nationwide Inpatient Sample: The Databases Used Affect Results in THA Research - Bekkers, Stijn (Springer US, 2014)
BACKGROUND: The National Hospital Discharge Survey (NHDS) and the Nationwide Inpatient Sample (NIS) collect sample data and publish annual estimates of inpatient care in the United States, and both are commonly used in orthopaedic research. However, there are important differences between the databases, and because of these differences, asking these two databases the same question may result in different answers. The degree to which this is true for arthroplasty-related research has, to our knowledge, not been characterized. QUESTION/PURPOSES: We tested the following null hypotheses: (1) there are no differences between the NHDS and NIS in patient characteristics, comorbidities, and adverse events in patients with hip osteoarthritis treated with THA, and (2) there are no differences between databases in factors associated with inpatient mortality, adverse events, and length of hospital stay after THA. METHODS: The NHDS and NIS databases use different methods of data collection and weighting to provide data representative of all nonfederal hospital discharges in the United States. In 2006 the NHDS database contained 203,149 patients with hip arthritis treated with hip arthroplasty, and the NIS database included 193,879 patients. Multivariable analyses for factors associated with inpatient mortality, adverse events, and days of care were constructed for each database. RESULTS: We found that 26 of 42 of the factors in demographics, comorbidities, and adverse events after THA in the NIS and NHDS databases differed more than 10%. Age and days of care were associated with inpatient mortality with the NHDS and the NIS although the effect rates differ more than 10%. The NIS identified seven other factors not identified by the NHDS: wound complications, congestive heart failure, new mental disorder, chronic pulmonary disease, dementia, geographic region Northeast, acute postoperative anemia, and sex, that were associated with inpatient mortality even after controlling for potentially confounding variables. For inpatient adverse events, atrial fibrillation, osteoporosis, and female sex were associated with the NHDS and the NIS although the effect rates differ more than 10%. There were different directions for sources of payment, dementia, congestive heart failure, and geographic region. For longer length of stay, common factors differing more than 10% in effect rate included chronic pulmonary disease, atrial fibrillation, complication not elsewhere classified, congestive heart failure, transfusion, discharge nonroutine compared with routine, acute postoperative anemia, hypertension, wound adverse events, and diabetes mellitus, whereas discrepant factors included geographic region, payment method, dementia, sex, and iatrogenic hypotension. CONCLUSIONS: Studies that use large databases intended to be representative of the entire United States population can produce different results, likely related to differences in the databases, such as the number of comorbidities and procedures that can be entered in the database. In other words, analyses of large databases can have limited reliability and should be interpreted with caution. LEVEL OF EVIDENCE: Level II, prognostic study. See the Instructions for Authors for a complete description of levels of evidence.